KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN SERTA HUBUNGANNYA DENGAN KEPUASAN KERJA KARYAWAN Dl STAI IBRAHIMY GENTENG KABUPATEN BANYUWANGI - Ahmad Hasyim Fauzan (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2014)
The purpose of this research is to analysis relationship betweenIndividual characteristics and job characteristics on jobsatisfaction in STAI Ibrahimy Genteng Banyuwangi. Thepopulation and sample in this research is all the employees inSTAI Ibrahimy about 46 employees, because of the population isless than 100 in its account, then the sample is taken from thatpopulation. This is a quantitatif rersearch with explanatorydesign with variable is X? (Individual characteristics), X2 (jobcharacteristics) and Y (job satisfaction). Collecting data methodsusing questionnaire which is given to the employees in STAIIbrahimy as the respondents than it is analyzed with pearsoncorrelation and multiple linear regression than it is proceed using17th version of SPSS software. The results of this study indicatethat: (1) there is a significant positive (p-0.000<0,05) relationshipbetween Individual characteristics and job characteristics on jobsatisfaction in STAI Ibrahimy Genteng Banyuwangi withcorrelation coefficient amounted 0,684 (2) there is a significantpositive (p-0,000<0.05) relationship between Individualcharacteristics and job characteristics on job satisfaction in STAIIbrahimy Genteng Banyuwangi with correlation coefficientamounted 0,521